Risk Aversion and Information Structure: An Experimental Study of Price Variability in the Securities Markets: Discussion - Cohen, Kalman J. (Journal of Finance, 1985)
Kalman J. Cohen, Risk Aversion and Information Structure: An Experimental Study of Price Variability in the Securities Markets: Discussion, The Journal of Finance, Vol. 40, No. 3, Papers and Proceedings of the Forty-Third Annual Meeting American Finance Association, Dallas, Texas, December 28-30, 1984 (Jul., 1985), pp. 845-846